2018
DOI: 10.1111/mms.12563
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population demography of narrow‐ridged finless porpoises from South Korea on the basis of mitochondrial DNA variation: Implications for its conservation in East Asia

Abstract: The narrow‐ridged finless porpoise, Neophocaena asiaeorientalis, is a small cetacean inhabiting the coastal waters of Taiwan, East China, Korea, and Japan, and is threatened by anthropogenic pressures. We analyzed the mitochondrial control region of N. asiaeorientalis from Korean waters to better understand the genetic diversity, population structure, and demographic history through comparison with previously reported sequences from Japan and China. The network and phylogenetic analyses illustrated that few co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 71 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…Cetaceans serve as umbrella species at the top of the marine ecosystem [38,39], playing a crucial role as keystone species that define the entire environmental conditions [40], including various factors such as micro-plastics, contaminants, epidemics, and pollution [41,42]. However, the NRFP is currently listed as an endangered species on the International Union for Conservation of Nature (IUCN) Red List, reflecting a significant decline in its population in recent years [43]. To address this issue, it is imperative to establish a continuous monitoring system for the NRFP population and the emergence of diseases within the marine environment of Korean seawater.…”
Section: Discussionmentioning
confidence: 99%
“…Cetaceans serve as umbrella species at the top of the marine ecosystem [38,39], playing a crucial role as keystone species that define the entire environmental conditions [40], including various factors such as micro-plastics, contaminants, epidemics, and pollution [41,42]. However, the NRFP is currently listed as an endangered species on the International Union for Conservation of Nature (IUCN) Red List, reflecting a significant decline in its population in recent years [43]. To address this issue, it is imperative to establish a continuous monitoring system for the NRFP population and the emergence of diseases within the marine environment of Korean seawater.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the Yangtze River was connected to the East China Sea through the paleo-river mouths, strengthening the connection between the epicontinental areas of the northern East China Sea and southern Yellow Sea [48]. The finless porpoise found in the BS is exclusively the narrow-ridged form, and it differs genetically from the porpoises seen around the Yangtze River mouth (the mid-East China Sea) and off the Korean coast in the Yellow Sea [27]. from Bohai Sea and wide-ridged finless porpoise (N. phocaenoides) from South China Sea (Pearl River Delta region).…”
Section: Sampling Locations and Sample Informationmentioning
confidence: 99%
“…The Taiwan Strait (TWS): two currently recognized species, the narrow-ridged and the wide-ridged finless porpoise inhabit waters of TWS and they appear to have been reproductively isolated since the LGM [24]. Occasional sally of species were seen, e.g., Lee et al [27] reported two wide-ridged finless porpoises stranded on Jeju Island, Korea, while narrow-ridged finless porpoises have been found stranded, albeit very rarely, in Hong Kong [29]. Whether these distant migrations can lead to efficient gene flow remains unknown.…”
Section: Sampling Locations and Sample Informationmentioning
confidence: 99%
See 2 more Smart Citations